Prawo do grobu jako problem kulturowy i prawny - Sobczak, Jacek; Gołda-Sobczak, Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Although the problem of death has long been bothering theologians, philosophers, psychologists, sociologists, anthropologists and culture experts, ultimately the regulation of areas related to the end of human life belongs to lawyers. They have to answer the questions when the human life ends and when the complex legal problems related to the protection of the deceased’s personal rights are solved. Although the family of the deceased is not in the possession of the deceased’s body, first and foremost the family own the right to decide on the deceased’s burial. This can of course cause conflicts. The right to the grave is personal and property. It is regulated by the Act of Law of January 31, 1959 about cemeteries and burial of deceased individuals. Of course, the funeral involves financial issues that do not constitute inheritance debt. In practice, serious difficulties may give rise to the will of the deceased as to the place or method of burial. Controversies can sometimes be aroused by the inscriptions on the tombstones, which involves the right to perform the worship of the deceased. The right to be buried by the immediate family of the deceased is a personal subjective right. The issue of exhumation is also important.